The Effect of Stories Using Hand Puppets on the Achievement of Moral Development in Children Aged 5 – 6 Years at Amir Hamzah Kindergarten - Nurkhaliza; Anita Yus (Indonesian Journal of Advanced Research, 2023)
In this study, the problem is the achievement of children's moral development that has not fully developed as expected.  This study aims to determine the effect of stories using hand puppet media on the achievement of moral development in children aged 5-6 years at Amir Hamzah Kindergarten. This study used an approach with an experimental method (Quasi Experimental Design) in the form of the equivalent Time Samples Design.  The population in this study were all children aged 5-6 years at Amir Hamzah Kindergarten with a sample of 9 children.  This research was conducted with 3 treatments.  data collection instruments using observation sheets.From the results of the data analysis, the data had an average value for treatment 1 of 7.44, then treatment 2 received a value of 9.667 while the third treatment had an average value of 11.777.  Based on data analysis through nonparametric hypothesis testing, the SPSS 22 statistic test value is 0.005.  Thus it can be concluded that stories using hand puppet media have a significant influence on the achievement of moral development in children aged 5-6 years at Amir Hamzah Kindergarten.